Third Order Hamiltonian for a Binary System with Varying Masses Including Preastron Effect - Al-Johani, Doaa Saleh; El-Saftawy, M. I. (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
This work concerns of the effects of the variation in the masses for two attracting bodies on the orbiter orbital elements. The formulation of the problem was done in different kind of mechanics, Newtonian, Lagrangian, and Hamiltonian. Moreover, constructing the Hamiltonian function of the varying masses of a binary system including, periastron effect, in canonical form in the extended phase space, up to third order of the small parameter ?, to be able to solve using canonical perturbation techniques. Canonical perturbation method based on Lee transformation was developed by Kamel used to remove the short periodic terms from the Hamiltonian to be able to solve the system of equations. The Hamiltonian of the system was transformed to the extended phase space by introducing two variable represents the variation of the masses and their conjugate momenta. Finally, Hamilton’s equation of motions was used to drive general formula to calculate the variations in the elements due to the variations in their masses and what so called periastron effects.